2017
DOI: 10.3390/w9070550
|View full text |Cite
|
Sign up to set email alerts
|

Source Water Protection Planning for Ontario First Nations Communities: Case Studies Identifying Challenges and Outcomes

Abstract: Abstract:After the Walkerton tragedy in 2000, where drinking water contamination left seven people dead and many suffering from chronic illness, the Province of Ontario, Canada implemented policies to develop Source Water Protection (SWP) plans. Under the Clean Water Act (2006), thirty-six regional Conservation Authorities were mandated to develop watershed-based SWP plans under 19 Source Protection Regions. Most First Nations in Ontario are outside of these Source Protection Regions and reserve lands are unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…Community members and practitioners indicated that Band Council does not have jurisdiction over these privately held lands; trying to develop a community-wide plan to regulate activities on-reserve is a source of tension and may be quite difficult when it comes to implementation. These findings are consistent with issues with CP lands reported by others [5].…”
Section: Challenges With Jurisdictionsupporting
confidence: 93%
See 2 more Smart Citations
“…Community members and practitioners indicated that Band Council does not have jurisdiction over these privately held lands; trying to develop a community-wide plan to regulate activities on-reserve is a source of tension and may be quite difficult when it comes to implementation. These findings are consistent with issues with CP lands reported by others [5].…”
Section: Challenges With Jurisdictionsupporting
confidence: 93%
“…Indigenous water insecurity is a serious issue impacting the health and wellbeing of Indigenous communities around the world [1][2][3][4][5]. In Canada, poor quality of drinking water has severely impacted many Indigenous communities across the country [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While provincial governments regulate water quality for off-reserve communities, there are no comparable regulations in place for water quality on First Nations reserves [6,17,52]. The responsibility for providing and maintaining clean water sources is often shared between Aboriginal Affairs and Northern Development Canada, Health Canada, Environment Canada and First Nations community leadership, which creates numerous challenges with accountability [7,53,54].…”
Section: First Nations Water Crisismentioning
confidence: 99%
“…In many cases, federal or provincial governance bodies have delegated water management responsibility to communities, based on the premise that local communities are well positioned to understand and address local water management challenges. Yet in this case, devolution of management authority has occurred as an unfunded mandate, since many local communities lack the financial and technical resources, as well as the governance capacity required to fully provide community water needs [7,8,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%